2016
DOI: 10.3389/fmicb.2016.01621
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Antimicrobial Susceptibility of Clostridium difficile Isolates from a University Teaching Hospital in China

Abstract: While the developed world has seen a significant increase in the number of scientific articles on Clostridium difficile infection (CDI), the developing world still lags behind on this subject due to limited laboratory capacity, low awareness, and limited surveillance of this problem. As such, CDI is considered a neglected but potentially huge problem in developing countries. The major aim of this study was to systemically evaluate the utility of several molecular typing tools for CDI, including their relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
4
26
2
2
Order By: Relevance
“…To reveal the epidemiology of CDI in mainland China, in this non-outbreak situation, specific genotypes of toxigenic C. difficile strains were observed. ST2 was the most predominant genotype, while recent studies reported that ST54, ST3 and ST37 were the most prevalent genotypes in mainland China [6,33,[36][37][38]. Noteworthily, in addition to ST54 and ST3, ST35 also emerged both in this work and another inspection in Yunnan [39], a province bordering Chongqing, witnessing the spread of this toxin genotype over provinces in China.…”
Section: Discussionsupporting
confidence: 51%
“…To reveal the epidemiology of CDI in mainland China, in this non-outbreak situation, specific genotypes of toxigenic C. difficile strains were observed. ST2 was the most predominant genotype, while recent studies reported that ST54, ST3 and ST37 were the most prevalent genotypes in mainland China [6,33,[36][37][38]. Noteworthily, in addition to ST54 and ST3, ST35 also emerged both in this work and another inspection in Yunnan [39], a province bordering Chongqing, witnessing the spread of this toxin genotype over provinces in China.…”
Section: Discussionsupporting
confidence: 51%
“…In this cross-sectional study, the major genotype for CDC was A+B+CDT-(87.13%), but no A-B+CDT-isolates, which were previously reported to be epidemic in Asia including parts of China, were detected (Collins et al, 2013;Cheng et al, 2016;Jin et al, 2017), showing significant regional variation in the genotype distribution of CD. Similarly, no CDT positive strains were detected, neither in studies conducted in northern China (Jin et al, 2017;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…And this has given a greater room for improvement in scientific discoveries [1]. Understanding the antimicrobial susceptility profiles for an organism is an important first step for studying epidemiology [7,15].…”
Section: In Epidemiological Studiesmentioning
confidence: 99%
“…The reasons are based on; the timely advantages, detection of slow growing pathogen or nonculturable organisms that are more or less difficult to detect, identify and even to be test for antimicrobial susceptibility by conventional methods [1][2][3][4][5]. This century is conciding with many highly infectious pathogens, notably HIV AIDS that has been dictating our immune response to the emerging of number of infections [2,3,[6][7][8][9][10]. Nowadays conditions such as HIV depends entirely on molecular diagnosis for susceptibility testing and management even during the acute phase [11].…”
Section: Introductionmentioning
confidence: 99%